2015
DOI: 10.1504/ijspacese.2015.073216
|View full text |Cite
|
Sign up to set email alerts
|

GPS-based orbital filter to reach the moon

Abstract: Nowadays, global navigation satellite systems (GNSSs) are used for many new applications that go further than the original goal of providing position, velocity and timing for land, maritime and air applications. In particular, GNSS receivers have been adopted as main navigation system for several low Earth orbits (LEOs) missions, increasing the autonomy of the hosting spacecraft, reducing the networking operation costs. Accordingly, they result in an attractive solution even for higher Earth orbits. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The full reference trajectory of the considered MTO has been validated using the much more accurate orbital propagator (HPOP) of the STK, which, unlike the one used by the orbital filter (to predict the GNSS observations), includes perturbations such as Earth gravitational potential spherical harmonics up to the 21st order and 21st degree, tidal forces, atmospheric drag, solar radiation pressure, and gravitational third‐body perturbation due to both the Moon and the Sun . The divergence between the trajectories generated under the orbital forces model used for the reference and the one used for the estimator in the orbital filter reaches almost 300 km at the end of MTO, as shown in Figure 7 of our previous work .…”
Section: Mission Scenario Descriptionsupporting
confidence: 53%
See 1 more Smart Citation
“…The full reference trajectory of the considered MTO has been validated using the much more accurate orbital propagator (HPOP) of the STK, which, unlike the one used by the orbital filter (to predict the GNSS observations), includes perturbations such as Earth gravitational potential spherical harmonics up to the 21st order and 21st degree, tidal forces, atmospheric drag, solar radiation pressure, and gravitational third‐body perturbation due to both the Moon and the Sun . The divergence between the trajectories generated under the orbital forces model used for the reference and the one used for the estimator in the orbital filter reaches almost 300 km at the end of MTO, as shown in Figure 7 of our previous work .…”
Section: Mission Scenario Descriptionsupporting
confidence: 53%
“…Several studies such as have shown the efficiency of using an orbital forces model to filter GNSS measurements for space navigation. Other studies such as have proved the feasibility of acquiring and tracking GNSS signals up to the Moon altitude, even if these signals are weak and affected by Doppler shifts and Doppler rates significantly higher than on Earth.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our previous study [13], we have also shown that, although more complex, filtering the raw pseudoranges and pseudorange rates can in general be more efficient, especially when less than four satellites are available (since the update of the estimations in the filter can still be achieved), leading to a higher navigation accuracy as also reported in [2]. A second version of the EKF filter using pseudoranges and pseudorange rates (as described in [3,4]) will thus be implemented in the WeakHEO 2 GPS receiver, currently under development, that will provide a ten times higher raw data output rate than the current platform.…”
Section: The Orbital Filtermentioning
confidence: 73%
“…The full reference trajectory of the considered MTO has been validated using the much more accurate orbital propagator (HPOP) of the STK, which, unlike the one used by the orbital filter (to predict the GNSS observations), includes perturbations such as Earth gravitational potential spherical harmonics up to the 21st order and 21st degree, tidal forces, atmospheric drag, solar radiation pressure, and gravitational third-body perturbation due to both the Moon and the Sun [8]. The divergence between the trajectories generated under the orbital forces model used for the reference and the one used for the estimator in the orbital filter reaches almost 300 km at the end of MTO, as shown in Figure 7 of our previous work [3].…”
Section: Reference Trajectorymentioning
confidence: 99%
See 1 more Smart Citation